Genes of the class II and class III major histocompatibility complex are associated with typhoid fever in Vietnam. - Dunstan, S; Stephens, H; Blackwell, J; Duc, C; Lanh, M; Dudbridge, F; Phuong, C; Luxemburger, C; Wain, J; Ho, V; Hien, T; Farrar, J; et al. (2001)
The influence of genes of the major histocompatibility complex (MHC) class II and class III loci on typhoid fever susceptibility was investigated. Individuals with blood culture-confirmed typhoid fever and control subjects from 2 distinct geographic locations in southern Vietnam were genotyped for HLA-DRB1 and HLA-DQB1 alleles, the gene that encodes tumor necrosis factor (TNF)-alpha (TNFA [-238] and TNFA [-308]), the gene that encodes lymphotoxin-alpha, and alleles of the TNF-alpha microsatellite. HLA-DRB1*0301/6/8, HLA-DQB1*0201-3, and TNFA*2 (-308) were associated with susceptibility to typhoid fever, whereas HLA-DRB1*04, HLA-DQB1*0401/2, and TNFA*1 (-308) were associated with disease resistance. The frequency of all possible haplotypes of the 3 individually associated loci were estimated and were found to be significantly different in typhoid case patients and control subjects (chi2=55.56, 32 df; P=.006). Haplotypes that were either protective (TNFA*1 [-308].DRB1*04) or predisposed individuals to typhoid fever (TNFA*2 [-308].DRB1*0301) were determined. This report identifies a genetic association in humans between typhoid fever and MHC class II and III genes.